Analisis Sentimen Calon Gubernur Jawa Timur 2018 di Twitter - Buntoro, Ghulam Asrofi (ScientiCO : Computer Science and Informatics Journal, 2018)
The East Java Governor Election 2018 is also felt in the virtual world especially Twitter. All people freely argue about their respective governor candidates, memorandum raises many opinions, not only positive or neutral also negative opinions. Media growth is so rapid, revealing a lot of online media from the news media to social media. Today's social media is not only used of friendship, but also for other activities. Promos of trading or buying and selling, until political party promos or campaigns of candidates for regents, governors, legislative candidates until presidential candidates. The research objective is to conduct a method of Sentiments Analysis for Governor candidates East Java 2018 in twitter with optimal and maximum optimization. While the benefits are to help the community conduct research on opinions on twitter which contains positive, neutral or negative sentiments. Sentiments Analysis for Governor candidates East Java 2018 in twitter using non-conventional processes that save costs, time and effort. The results of Khofifah's dataset are 77% accuracy, 79.2% precision, 77% recall, 98.6% TP rate and 22.2% TN rate. For the results of GusIpul dataset, accuracy is 76%, precision 74.4%, recall 76%, the TP rate is 93.8% and the TN rate is 52.9%.